Perspective: Does Realism Improve Presence in VR? Suggesting a Model and Metric for VR Experience Evaluation - Jung, Sungchul; Lindeman, Robert. W (Frontiers in Virtual Reality, 2021)
The concepts of "immersion" and "presence" have been considered as staple metrics for evaluating the quality of virtual reality experiences for more than five decades, even as the concepts themselves have evolved in terms of both technical and psychological aspects. To enhance the user's experience, studies have investigated the impact of different visual, auditory, and haptic stimuli in various contexts to mainly explore the concepts of "plausibility illusion" and "place illusion". Previous research has sometimes shown a positive correlation between increased realism and an increase in presence, but not always, and thus, very little of the work around the topic of presence reports an unequivocal correlation. Indeed, one might classify the overall findings within the field around presence as "messy". Better (or more) visual, auditory, or haptic cues, or increased agency, may lead to increased realism, but not necessarily increased presence, and may well depend on the application context. Rich visual and audio cues in concert contribute significantly to both realism and presence, but the addition of tactile cues, gesture input support, or a combination of these might improve realism, but not necessarily presence. In this paper, we review previous research and suggest a possible theory to better define the relationship between increases in sensory-based realism and presence, and thus help VR researchers create more effective experiences.